2019
DOI: 10.1167/iovs.19-27539
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Retinal Nerve Fibers From Emmetropia Through to High Myopia at Both the Temporal Raphe and Optic Nerve

Abstract: Citation: Bedggood P, Mukherjee S, Nguyen BN, Turpin A, McKendrick AM. Geometry of the retinal nerve fibers from emmetropia through to high myopia at both the temporal raphe and optic nerve. Invest Ophthalmol Vis Sci. 2019;60:4896-4903. https://doi.org/10.1167/iovs.19-27539 PURPOSE. The geometry of retinal nerve fibers may be altered with myopia, a known risk factor for glaucoma. Recent developments in high resolution imaging have enabled direct visualization of nerve fiber bundles at the temporal raphe wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Patients with high myopia usually have a distorted optic disc, peripapillary atrophy, and posterior scleral staphyloma, which may interfere with the accuracy of RNFL thicknesses measured by OCT and glaucoma severity evaluation, as assessed by ophthalmologists. Low concordance to ISNT and related rules was observed in myopia (e.g., for RNFL, 8% of high axial myopes compared with 67% of emmetropes 20 ). Furthermore, visual eld examination of patients with high myopia often shows declining visual sensitivity and/or local visual eld loss, which would also disturb the judgment of glaucomatous visual eld defects.…”
Section: Discussionmentioning
confidence: 94%
“…Patients with high myopia usually have a distorted optic disc, peripapillary atrophy, and posterior scleral staphyloma, which may interfere with the accuracy of RNFL thicknesses measured by OCT and glaucoma severity evaluation, as assessed by ophthalmologists. Low concordance to ISNT and related rules was observed in myopia (e.g., for RNFL, 8% of high axial myopes compared with 67% of emmetropes 20 ). Furthermore, visual eld examination of patients with high myopia often shows declining visual sensitivity and/or local visual eld loss, which would also disturb the judgment of glaucomatous visual eld defects.…”
Section: Discussionmentioning
confidence: 94%
“…Hence we can't distinguish that the declined thickness of inner retinal layers (including RNFL and GCIPL) in glaucoma patients with high myopia is due to increasing axial lengths or glaucomatous defects [16,17]. Additional low concordance to the rules of inferior>superior>nasal>temporal (ISNT) was observed in myopia (e.g., for RNFL, 8% of high axial myopes compared with 67% of emmetropes [18]). Furthermore, visual field examination of patients with high myopia often shows declining visual sensitivity and/or local visual field loss, which would also disturb the judgment of glaucomatous visual field defects.…”
Section: Discussionmentioning
confidence: 96%
“…Using an adaptiveoptics scanning laser ophthalmoscope, Huang et al 9 reported this angle to be 170.3°± 3.6°. Using OCT, Tanabe et al 10 found 169°± 3°and Bedggood et al [11][12][13] found 173°± 3°. With a disc-fovea angle of 7.6°(see next paragraph), our reference line (black line in Fig.…”
Section: Discussionmentioning
confidence: 99%